Wildhood [videorecording (DVD)] - Hannam, Bretten; Lewitski, Phillip; Odjick, Joshua; Lund, Steve, 1989-; Greyeyes, Michael; Spracklin, Savonna; Hynes, Joel Thomas (Wolfe Video, 2022)
Two brothers reconnect with their indigenous Mi'kmaq heritage and find a new friend while on a search for their birth mother.